Implementasi Perpindahan Warisan Pusaka Tinggi Menjadi Pusaka Rendah dalam Adat Minangkabau Perspektif Maqāṣid al-Syarī‘ah: Implementation of the Transformation of Pusaka Tinggi Inheritance into Pusaka Rendah in Minangkabau Custom from the Perspective of Maqāṣid al-Syarī‘ah - Wulandari Binti Zulfadli; Oktaviani, Witia (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
This study aims to examine the transformation of high heritage property into low heritage property in Kenagarian Sumani as a form of community adaptation to social dynamics. The study focuses on the factors that drive the change in the status of inheritance from high heritage property to low heritage property, as well as the practices involved. The phenomenon is then analysed from the perspective of maqāṣid al-syarī‘ah to evaluate its alignment with the objectives of Islamic law in achieving the best interests of those involved in the inheritance process. This study uses a qualitative approach with a case study design. Data were collected through interviews with niniak mamak, traditional leaders, and local residents, as well as through an analysis of various sources of customary law and Islamic literature. The results of the study show that the change in status from high to low heritage is made to prevent family conflict. This change has a positive impact on ownership clarity and family harmony, despite reducing the traditional value of high-status property as a symbol of identity. From a sharia perspective, this shift is in line with the Islamic sharia's goal of safeguarding property, lineage, life, intellect and religion, illustrating the adaptive interaction between customary law and Islamic legal objectives.